PERINGKAT OBLIGASI PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA : BOND RATINGS ON CONSTRUCTION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Simatupang, Idul Fazri; Naz'aina, Naz'aina (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
The purpose of this study is to see how profitability, leverage, liquidity, and receivables turnover affect bond ratings for construction companies listed on the Indonesian stock exchange from 2010 to 2020. In this study the sample were 33 construction companies. The sampling method used purposive sampling. Relationship and (or) influence between variable is described by using multiple linier regression analysis. The result indicted that Leverage and Turnover of Receivables had significant positive while Liquidity and Profitability had insignificantly in the bond rating